Desenvolvimento de metodologia para análise de arborescências em materiais dielétricos por contraste de fase de raios X - Ribeiro Júnior, Sebastião (2013)
The water tree or electrical tree occurrence is identified as the main phenomena in the degradation in solid isolations of the electric energy distribution cables. The water tree evolution can lead to dielectric breakdown of the isolation layer and, consequently, to the failure this equipment and the interruption of the electric energy supply. The understanding this phenomenon is necessary for the development analysis methods and to prevent collapse in the polymeric insulation. This work demonstrates the application of X-ray phase contrast technique as a methodology for the study of the water tree and electrical tree in Ethylene propylene rubber (EPR) and crosslinked polyethylene (XLPE).